An Evaluation of Health Care Waste Generation and Disposal at Ramadi Teaching Hospital in Iraq - Thameel, Salah; Al-Chalabi, Saeb; Mustafa, Ayad; Mohsin, Ahmed (Iraqi Journal of Civil Engineering, 2022)
In recent years, hospital waste has been one of the most serious issues in Iraq and other parts of the world. The current study aims to measure and analyze hospital waste output across all departments at the Ramadi Teaching Hospital. The data on waste generation rates gathered for the study were primarily based on existing records of field management of hospital waste over the course of eight months (one week per month) for all departments in the hospital; however, some random sampling information was provided to supplement the data. The results revealed that the estimated rate of medical waste creation at Ramadi hospital was between 144 and 188 kg/day, whereas the general (non-medical) waste generation was between (240-278) kg/day. In terms of patient numbers and per occupied bed, the average medical waste generation rates were from 0.60 to 0.90 kg/patient/day and (0.85-1.11) kg/bed/day, respectively, whereas the average general trash generation rates ranged from 0.86 to 1.15 kg/patient/day and 1.42-1.64 kg/bed/day. The recent analysis concluded that the hospital’s segregation procedure is still inefficient, and there is room for improvement in terms of reducing hazardous medical waste creation